A Feasibility Randomized Controlled Crossover Trial of Home-Based Warm Footbath to Improve Sleep in the Chronic Phase of Traumatic Brain Injury. Issue 6 (December 2017) - Chiu, Hsiao-Yean; Lin, En-Yuan; Chiu, Hsiao-Ting; Chen, Pin-Yuan
Abstract : ABSTRACT: Introduction: Sleep disturbance is a common complaint after traumatic brain injury (TBI). The aim of this study was to examine the effects of a home-based warm footbath intervention on sleep in patients with TBI.Methods: This was a randomized controlled crossover study, and 23 adults with TBI were recruited and randomized to receive first a 30-minute, 41°C warm footbath and then a usual care, or vice versa, with each lasting 3 days and separated by a 3-day washout. Sleep efficiency, sleep onset latency (SOL), total sleep time, and wake after sleep onset (WASO) were assessed by actigraphy.Results: We found that home-based warm footbath significantly had a reduced SOL (difference, −5.11 minutes) and a suppressed WASO (difference, −2.57 minutes) compared with those of usual care, but not in sleep efficiency and total sleep time. No adverse effect was reported.Conclusions: This study suggested that home-based warm footbath is practical and effective in relieving post-TBI sleep disturbances, particular in SOL and WASO. Nurses can use home-based warm footbath as an effective intervention for management of sleep disturbances after TBI.